Effects of Sewage Sludge Applications on the Yield and Trace Element and Heavy Metal Accumulation in Peanut (Arachis hypogaea L.) - DELIBACAK, SEZAI; OKUR, BULENT; YAGMUR, BULENT; RIZA ONGUN, ALI (Asian Journal of Chemistry, 2010)
In this research, effects of different sewage sludge (biosolid) levels on the yield and trace element and heavy metal acumulation in peanut were investigated. The experiment was conducted using a randomized block design with 4 replicates in Menemen Plain, in the Western Anatolia region of Turkey in year 2003 and 2004. Wet sewage sludge was added to the soil at the rates of 0, 30, 60, 90 t ha-1. The results showed that increasing sewage sludge application to Typic Xerofluvent soil significantly increased peanut yield, Fe, Cu and Ni content of edible part of peanut in 2003 and 2004, but did not significantly affect Mn, Zn, Cd, Cr, Pb contents of peanut in same years. Meanwhile, trace elements and heavy metals (Fe, Cu, Mn, Zn, Co, Cd, Cr, Ni, Pb) concentrations of peanut were found under threshould values.